The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1097/aln.0000000000002195
|View full text |Cite|
|
Sign up to set email alerts
|

Free Fatty Acid Receptor G-protein–coupled Receptor 40 Mediates Lipid Emulsion-induced Cardioprotection

Abstract: Background We have previously shown that intralipid (lipid emulsion) protects the heart against ischemia/reperfusion injury and bupivacaine-induced cardiotoxicity. However, the precise underlying mechanisms are not fully understood. Here we explored the hypothesis that free fatty acid receptor-1 or G-protein–coupled receptor 40 is expressed in the heart and that cardioprotective effects of lipid emulsion are mediated through G-protein–coupled receptor 40 in two animal models of ischemia/reper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 31 publications
0
22
0
Order By: Relevance
“…Because patients with local anesthetic-induced cardiac arrest are considered to be less responsive for standard resuscitation methods, currently infusion of lipid emulsion is considered the primary treatment for local anesthetic toxicity [10,11]. In recent years, another striking experimental finding is that intralipid postconditioning(ILPC) could reduce myocardial I/R injuries and thus improve cardiac function, where intralipid was administered as a bolus at the onset of reperfusion [12][13][14][15][16][17]. So, intralipid may represents a novel and clinically feasible cardioprotective strategy that is highly effective in remodeled hearts.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Because patients with local anesthetic-induced cardiac arrest are considered to be less responsive for standard resuscitation methods, currently infusion of lipid emulsion is considered the primary treatment for local anesthetic toxicity [10,11]. In recent years, another striking experimental finding is that intralipid postconditioning(ILPC) could reduce myocardial I/R injuries and thus improve cardiac function, where intralipid was administered as a bolus at the onset of reperfusion [12][13][14][15][16][17]. So, intralipid may represents a novel and clinically feasible cardioprotective strategy that is highly effective in remodeled hearts.…”
Section: Discussionmentioning
confidence: 99%
“…It has also played an important role in rescuing the cardiac arrest caused by local anesthetic toxicity, which has been incorporated into several clinical guidelines [8][9][10][11]. In recent years, experimental studies have shown that lipid emulsion infusion just before reperfusion (i.e., intralipid postconditioning, ILPC) could reduce myocardial infarct sizes, improve cardiac function and reduce myocardial I/R injuries [12][13][14][15][16]. Subsequent mechanistic studies define that ILPC acts through the phosphorylation of glycogen synthase kinase-3β via PI3K/Akt/ERK pathways [12][13][14], Caveolin2/STAT3/GSK-3β pathway [15], and ultimately inhibits the opening of mitochondrial permeability transition pore (mPTP), which is essential to mitochondrial calcium overload and reactive oxygen species (ROS).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also played an important role in rescuing the cardiac arrest caused by local anesthetic toxicity, which has been incorporated into several clinical guidelines [8][9][10][11]. In recent years, experimental studies have shown that lipid emulsion infusion just before reperfusion (i.e., intralipid postconditioning, ILPC) could reduce myocardial infarct sizes, improve cardiac function and reduce myocardial I/R injuries [12][13][14][15][16]. Subsequent mechanistic studies de ne that ILPC acts through the phosphorylation of glycogen synthase kinase-3β via PI3K/Akt/ERK pathways [12,14,15], Caveolin2/STAT3/GSK-3β pathway [13], and ultimately inhibits the opening of mitochondrial permeability transition pore (mPTP), which is essential to mitochondrial calcium overload and reactive oxygen species (ROS).…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent mechanistic studies de ne that ILPC acts through the phosphorylation of glycogen synthase kinase-3β via PI3K/Akt/ERK pathways [12,14,15], Caveolin2/STAT3/GSK-3β pathway [13], and ultimately inhibits the opening of mitochondrial permeability transition pore (mPTP), which is essential to mitochondrial calcium overload and reactive oxygen species (ROS). Meanwhile, Umar [16] reported that the cardioprotective effects of lipid emulsion are mediated through G-protein coupled receptor-40 (GPR40) in two animal models of I/R injury and bupivacaine-induced cardiotoxicity.…”
Section: Introductionmentioning
confidence: 99%